INFORMATION SEEKING BEHAVIOR AS A MEDIATOR: THE INFLUENCE OF SOCIAL MEDIA DEPENDENCE ON THE VOTING BEHAVIOR OF MIGRANT STUDENTS - Salsabila Anya Annora; Rina Martini (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to analyze the influence of social media dependence and Information Seeking Behavior on the voting behavior of migrant students in the 2024 Election in Salatiga City. Using a quantitative approach, data were collected through an online questionnaire from 209 migrant student respondents from two major universities in Salatiga. The analysis was conducted using Structural Equation Modeling based on Partial Least Squares (SEM-PLS) to test the direct and indirect relationships between variables. The results revealed that social media dependence has a positive and significant effect on voting behavior, both directly and indirectly through the mediation of ISB. Key findings indicate that ISB acts as a strong partial mediator, meaning that the influence of social media on election decisions is largely carried out through an active and critical information search process as modeled by Ellis. This study provides a theoretical contribution by integrating Media Dependency Theory and Ellis's Model to understand the mechanisms of voter behavior in the digital era, as well as practical implications for election organizers and educational institutions in designing effective political communication and digital literacy strategies for young migrant voters.